TECHNOLOGY OF STORAGE OF ROOTS OF OSH BAKED BEANS IN TEMPORARY STORAGE (Bulletin of Innovative Research, 2026)
The technology of storing beetroot in temporary storage is covered. The study analyzed the morpho-biological properties of beetroot, its requirements for respiration intensity, humidity and temperature, and physiological and biochemical changes occurring during storage. The optimal storage regimes in temporary storages (above-ground and semi-underground piles, trenches) are justified - the temperature should be 0…+2 °C, relative humidity 85–95%. It serves to develop scientifically based recommendations to maintain quality indicators (dry matter, sugar content, appearance) and minimize losses during storage in temporary storages.